1996
DOI: 10.1093/nar/24.9.1682
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Footprinting of the Mouse Inducible Nitric Oxide Synthase Gene: Inducible Protein Occupation of Numerous Sites Including Oct and NF-IL6

Abstract: A wide variety of cells usefully but sometimes destructively produce nitric oxide via inducible nitric oxide synthase (iNOS). Data obtained by gel shift analysis and reporter assays have linked murine iNOS gene induction by cytokines and bacterial products with the binding of a number of proteins to a proximal promoter, as well as to a distal enhancer of the iNOS gene. Nevertheless, these techniques do not necessarily reflect protein occupation of sites in vivo. To address this, we have used dimethyl sulphate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 34 publications
3
66
0
Order By: Relevance
“…These results suggest that C 2 -ceramide inhibition of LPSdependent signaling cascades leading to iNOS gene induction is dependent on the types of macrophages. Actually it is known that the iNOS gene is regulated by several coordinated transcription factors (63,64) and is distinctly induced in different cell types. For example, priming factors, such as IFN-␥, IL-1, TNF-␣, and Ca 2ϩ , are required for the maximal induction of iNOS expression in peritoneal macrophages (33,34,65) and C 6 -glioma cells (66).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that C 2 -ceramide inhibition of LPSdependent signaling cascades leading to iNOS gene induction is dependent on the types of macrophages. Actually it is known that the iNOS gene is regulated by several coordinated transcription factors (63,64) and is distinctly induced in different cell types. For example, priming factors, such as IFN-␥, IL-1, TNF-␣, and Ca 2ϩ , are required for the maximal induction of iNOS expression in peritoneal macrophages (33,34,65) and C 6 -glioma cells (66).…”
Section: Discussionmentioning
confidence: 99%
“…The murine iNOS promoter contains 12 nucleotide sequences that conform to the consensus C/EBP␤ box TKNNGYAAK (43). Using footprinting analysis of the 5Ј-flanking region of the iNOS gene in activated RAW 264.7 cells, Goldring et al (41) have also demonstrated protection of guanine 146 within the C/EBP␤ box, suggesting that C/EBP␤ binds to this site. In addition, correlative changes in the activation of C/EBP␤ and the expression of the iNOS gene in cultured cardiac myocytes and vascular smooth muscle cells (40,42) provided evidence to suggest a role for C/EBP␤ in the expression of iNOS.…”
Section: Cd40 Ligation Stimulates the Production Of No In Ifn-␥-treatmentioning
confidence: 99%
“…iNOS is one of several TNF-regulated genes that are known to protect hepatocytes from LPS toxicity (50 -52). Moreover, LPS-mediated transcriptional activation of the murine iNOS gene requires TNF-initiated signals that enhance NF-B activity (53)(54)(55). LPS increases iNOS mRNA levels similarly in ethanol-and pair-fed mice (Fig.…”
Section: Induction Of Nf-b and Inos An Nf-b Targetmentioning
confidence: 99%